STRATEGI LIVE COMMERCE PADA UMKM DI KABUPATEN BANYUMAS - Putri, Puspita Lianti; Indrawati, Iin Dyah (LPPM Universitas Harapan Bangsa, 2025)
The growth of social commerce has accelerated live commerce as a marketing channel that emphasizes real time interaction, product demonstration, and trust building. This article aims to explain how live commerce is enacted as a strategic marketing and business practice among MSMEs in Banyumas Regency. Adopting an interpretive qualitative perspective with a multiple case study design, the study synthesizes two data sources: published MSME case studies containing interviews, observations, and documentation from the Banyumas context, and TikTok Shop analytics including performance records of TikTok Shop LIVE sessions from accounts identified with Banyumas or Purwokerto. Data were analyzed using reflexive thematic analysis to identify recurring strategic practices across cases. The findings reveal five core themes: structuring live sessions to capture attention and sustain audience engagement; transparency and demonstration as foundations of trust; conversion mechanisms driven by promotional urgency and explicit calls to action; live commerce as an ecosystem hub connected to broader sales networks such as resellers and affiliates; and operational capability and role division as prerequisites for sustainability. Platform analytics further show sharp performance variation, suggesting that higher live frequency does not automatically translate into higher transaction value. Overall, live commerce among Banyumas MSMEs constitutes a strategic capability that requires orchestration of content, trust, and operational consistency. The study highlights practical implications for capacity building that goes beyond technical livestream skills toward content strategy, promotional governance, service management, and transaction channel integration.